2012
DOI: 10.1002/adsc.201100862
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of N‐Substituted Planar Chiral Ferrocenes Using a Proline Hydantoin‐Derived Auxiliary

Abstract: An N-substituted ferrocene bearing a proline-derived chiral directing group undergoes diastereoselective lithiation-electrophile quench to give planar chiral products in > 95:5 dr. The starting material is synthesized by imidation of iodoferrocene with l-proline hydantoin, followed by hydrosilylation. Although the auxiliary is stable to lithium bases of the types RLi and R 2 NLi, the ortho-substituted products may be converted to solely planar chiral derivatives with simple reagents thanks to a labile triethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…50-60%). These results mirrored the behavior of syn-13 with bases other than t-BuLi [14] and suggested that the origin of stereoselectivity for both substrates was Cp ring-controlled.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…50-60%). These results mirrored the behavior of syn-13 with bases other than t-BuLi [14] and suggested that the origin of stereoselectivity for both substrates was Cp ring-controlled.…”
Section: Resultssupporting
confidence: 78%
“…As anticipated based on the crystal structure for 16a, products ent-18a-c were enantiomers of the imidazolones derived previously from syn-13 (17a-c!18a-c), as measured by specific rotation and chiral stationary phase HPLC analysis. [14] It is clear from these results that the configuration of the silyloxy-containing b-ferrocenyl stereogenic center is the primary determinant of the sense of planar chiral induction in these substrates.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations